Principles and Practice of Urogynaecology - Tamilselvi, A.; Rane, Ajay (Springer India : Imprint: Springer, 2015)
Despite the wide prevalence of urogynaecological problems, in clinical practice, there is a paucity of specialists that are skilled in the management of these conditions. The recognition of the need for a specialist to deal with these specific problems has led to the recent evolution of urogynaecology as a subspecialty. This book, Principles and Practice of Urogynaecology, aims to equip the practicing professionals - Gynaecologists, Urogynaecologists and Urologists, with up-to-date information on the principles that guide the evaluation and management of pelvic organ prolapse and other common urogynaecological problems. With an emphasis on evidence based medicine, the book aims to deliver guidance on management of common urogynaecological problems and provides information on the latest cutting-edge surgical techniques. Written by global experts in the field of urogynaecology, the book focuses initially on pelvic floor anatomy and function, moving seamlessly to the evaluation and management of clinically relevant pelvic floor problems. A detailed discussion on management of mesh related complications is a highlight. .